Komplikasi Muskuloskeletal pada Pasien Diabetes Melitus - Dirga Yudha Prakasa (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background. Apart from macrovascular and microvascular complications, diabetic patients may experience some musculoskeletal complications. The impact of musculoskeletal complications on the quality of life of diabetics is enormous. There are many epidemiological data linking this complication to diabetes, but the pathogenesis and causative factors have not been elucidated. Therefore, the aim of this literature study is to further investigate musculoskeletal complications in diabetes mellitus patients. Method. This study is a literature review, with 18 literature sources, from 1 national journal and 17 international journals. Result. Several studies have shown that musculoskeletal complications that are often found in people with diabetes mellitus include shoulder capsulitis, limited joint mobility syndrome, Dupuytren's contracture, carpal tunnel syndrome and trigger finger. Vascular and nerve damage, protein glycosylation, and increased collagen in the skin and musculoskeletal connective tissue are some of the factors thought to contribute to the development of musculoskeletal disorders in diabetics. Conclusion. The musculoskeletal manifestations of diabetes are common, and although they are not life threatening, they are an important cause of morbidity, pain and disability. Keywords: diabetes mellitus, complications, musculoskeletal.